2017
DOI: 10.1002/anie.201702406
|View full text |Cite|
|
Sign up to set email alerts
|

A Highly Active Manganese Catalyst for Enantioselective Ketone and Ester Hydrogenation

Abstract: A new hydrogenation catalyst based on a manganese complex of a chiral P,N,N ligand has been found to be especially active for the hydrogenation of esters down to 0.1 mol % catalyst loading, and gives up to 97 % ee in the hydrogenation of pro-chiral deactivated ketones at 30-50 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(134 citation statements)
references
References 76 publications
3
129
1
1
Order By: Relevance
“…The catalyst is less active with ortho ‐substituted substrates ( 3 b , 3 e , 3 i ), probably because of steric effects, but increasing the reaction time from 3 to 6 hours gives good yields (88–98 % yield). Notably, the 2,6‐methoxy‐disubstituted ketone 3 h is reduced at 80 °C within 9 hours with 61 % yield and 97 % ee , which is unprecedented with Mn I . In addition to alkyl and alkoxy substituents, halogen substituents ( 3 i – n ) are tolerated (90–97 % ee ).…”
Section: Figurementioning
confidence: 97%
“…The catalyst is less active with ortho ‐substituted substrates ( 3 b , 3 e , 3 i ), probably because of steric effects, but increasing the reaction time from 3 to 6 hours gives good yields (88–98 % yield). Notably, the 2,6‐methoxy‐disubstituted ketone 3 h is reduced at 80 °C within 9 hours with 61 % yield and 97 % ee , which is unprecedented with Mn I . In addition to alkyl and alkoxy substituents, halogen substituents ( 3 i – n ) are tolerated (90–97 % ee ).…”
Section: Figurementioning
confidence: 97%
“…[16] In 2016, Milstein and co-workers reported the first manganese-catalyzed ADC of alcohols with amines. [28] Based on the borrowing hydrogen approach, Calkylations of ketones [29] and Nalkylations of amines [30] have also been developed. [28] Based on the borrowing hydrogen approach, Calkylations of ketones [29] and Nalkylations of amines [30] have also been developed.…”
mentioning
confidence: 99%
“…[10a,23] Gratifyingly,at608 8C, in toluene,inthe presence of 1.0 mol % of 2 and 2.0 mol %o fK HMDS,a cetophenone was fully reduced to 1-phenylethanol (see Table S1 for optimization details). [10,23,24] We then enlarged the synthetic scope of this catalytic transformation ( Table 1) and found that al arge variety of aryl(alkyl)ketones could be readily reduced (entries 1-18), including sterically hindered representatives (entries 2-4, 7) inaccessible using our previous Mn catalyst based on achelating phosphine-aminopyridine ligand. Am aximum TONo f6 200 was achieved with 0.01 mol %i nt-AmOH, showing that this catalyst is competitive with the best Mnbased systems for this reaction reported to date [23b-c] No reaction took place in the presence of the sole hydride complex 3,w hile catalytic activity could be restored in the presence of base,s howing its critical role in the catalytic cycle.…”
Section: Methodsmentioning
confidence: 99%